Expect Fibonacci

Calculus Level 4

Let F n F_n denote the n th n^\text{th} Fibonacci number , where F 1 = 1 , F 2 = 1 , F_1 = 1, F_2 = 1, and F n + 2 = F n + 1 + F n F_{n+2} = F_{n+1} + F_{n} for n = 1 , 2 , 3 , . n=1,2,3,\ldots.

Define f n ( x ) f_n (x) as a least-degree polynomial that passes through the coordinates ( x , y ) = ( 1 , F 1 ) , ( 2 , F 2 ) , ( 3 , F 3 ) , , ( n 1 , F n 1 ) . (x,y)= (1, F_1), (2,F_2) , (3,F_3) , \ldots , (n-1, F_{n-1}). Hence, we define the expected Fibonacci sequence e F n ^e F_n to be equal to f n ( n ) . f_n (n).

For example, with F 1 = F 2 = 1 F_1 = F_2 = 1 and F 3 = 2 , F_3 = 2, we have f 4 ( x ) = 1 2 ( x 2 3 x + 4 ) , f_4 (x) = \frac12\big(x^2-3x+4\big), so e F 4 = f 4 ( 4 ) = 4. ^e F_4 = f_4 (4) = 4.

Find the closed form of the limit below (submit your answer to three decimal places): lim n e F n F n F n . \lim_{n\to\infty} \dfrac{ \big|^e F_n - F_n \big|}{F_n}.

Notation: | \cdot | denotes the absolute value function .


The answer is 0.381966.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

John Ross
Jun 18, 2018

We will use n=10 as an example, and it is easy to see that this method generalizes to all other n. We can use a difference table to find the polynomial that passes through the first nine points (i.e. f 10 ( x ) f_{10} (x) ). 1 0 1 1 2 3 5 8 13 1 1 0 1 1 2 3 5 2 1 1 0 1 1 2 3 2 1 1 0 1 5 3 2 1 1 8 5 3 2 13 8 5 21 13 34 \begin{array}{c}\\ 1&0&1&-1&2&-3&5&-8&13 \\ 1&1&0&1&-1&2&-3&5 \\ 2&1&1&0&1&-1&2 \\ 3&2&1&1&0&1 \\ 5&3&2&1&1 \\ 8&5&3&2 \\ 13&8&5 \\ 21&13 \\ 34 \end{array} Because this is a degree 8 polynomial, the 8th column (after the initial column) will be constant, so we can put another 13 below the last 13 in the table and work backwards to find f 10 ( 10 ) f_{10} (10) . 1 0 1 1 2 3 5 8 13 1 1 0 1 1 2 3 5 13 2 1 1 0 1 1 2 18 3 2 1 1 0 1 20 5 3 2 1 1 21 8 5 3 2 22 13 8 5 24 21 13 29 34 42 76 \begin{array}{c}\\ 1&0&1&-1&2&-3&5&-8&13 \\ 1&1&0&1&-1&2&-3&5&13 \\ 2&1&1&0&1&-1&2&18 \\ 3&2&1&1&0&1&20 \\ 5&3&2&1&1&21 \\ 8&5&3&2&22 \\ 13&8&5&24 \\ 21&13&29 \\ 34&42 \\ 76 \end{array} Notice that f 10 ( 10 ) f_{10} (10) was just the number that we placed under the final 13 (which in this case happened to also be a 13) plus the entire diagonal. In other words if we changed the number we placed below the final 13 by a certain amount, it would change f 10 ( 10 ) f_{10} (10) by the same amount. Now we just need to think about what number we would have placed in that spot if we wanted the actual Fibonacci sequence, not the expected Fibonacci sequence. It is easy to see that because we are taking the forward difference to obtain the next column in the difference table, each column is the Fibonacci sequence shifted down. This means that the rows are the Fibbonacci sequence extended in the negative direction (also the Fibonacci sequence with alternating signs). Thus we can see that we would have placed a -8, not a 13 in the final spot, giving the difference between expected and actual Fibonacci of 8+13=21 (this generalizes for all n, the only difference being sign changes, but the absolute value function takes care of that). This is the definition for the next Fibbonaci number (after 8 and 13), so e F n F n = F n 2 \big|^e F_n - F_n \big|=F_{n-2} The ratio between large Fibonacci numbers approaches ϕ = 1 + 5 2 \phi=\frac{1+\sqrt5}2 , so our answer is 1 ϕ 2 0.381966 \frac{1}{\phi^2} \approx 0.381966

Also phi^(-2)=2-phi=(3-sqrt(5))/2 (just to know the exact form).

Pau Cantos - 2 years, 11 months ago
Mark Hennings
Jun 1, 2018

Let G n ( X ) G_n(X) be the polynomial of degree n 1 n-1 such that G n ( j ) = F j G_n(j) = F_j for 1 j n 1 \le j \le n . Lagrangian interpolation gives us that G n ( X ) = u = 1 n F u 1 v n v u X v u v = u = 1 n F u ( 1 ) n u ( u 1 ) ! ( n u ) ! 1 v n v u ( X v ) = 1 ( n 1 ) ! u = 1 n ( 1 ) n u ( n 1 u 1 ) F u 1 v n v u ( X v ) \begin{aligned} G_n(X) & = \; \sum_{u=1}^n F_u \prod_{{1 \le v \le n} \atop {v \neq u}} \frac{X-v}{u-v} \; = \; \sum_{u=1}^n \frac{F_u}{(-1)^{n-u}(u-1)!(n-u)!}\prod_{{1 \le v \le n} \atop {v \neq u}} (X-v) \\ & = \; \frac{1}{(n-1)!} \sum_{u=1}^n (-1)^{n-u}\binom{n-1}{u-1}F_u \prod_{{1 \le v \le n} \atop {v \neq u}}(X-v) \end{aligned} and so the leading coefficient of G n ( X ) G_n(X) is α n = 1 ( n 1 ) ! u = 1 n ( 1 ) n u ( n 1 u 1 ) F u \alpha_n \; = \; \frac{1}{(n-1)!}\sum_{u=1}^n (-1)^{n-u}\binom{n-1}{u-1}F_u Using Binet's Formula for the Fibonacci numbers, and writing ϕ = 1 2 ( 1 + 5 ) \phi = \tfrac12(1 + \sqrt{5}) and ψ = 1 2 ( 1 5 ) \psi = \tfrac12(1 - \sqrt{5}) , we see that α n = 1 5 ( n 1 ) ! u = 1 n ( 1 ) n u ( n 1 u 1 ) [ ϕ u ψ u ] = 1 5 ( n 1 ) ! u = 0 n 1 ( 1 ) n 1 u ( n 1 u ) [ ϕ u + 1 ψ u + 1 ] = 1 5 ( n 1 ) ! [ ϕ ( ϕ 1 ) n 1 ψ ( ψ 1 ) n 2 ] = 1 5 ( n 1 ) ! [ ϕ ( ψ ) n 1 ψ ( ϕ ) n 1 ] = 1 5 ( n 1 ) ! [ ( ψ ) n 2 ( ϕ ) n 2 ] = ( 1 ) n 1 5 ( n 1 ) ! [ ϕ n 2 ψ n 2 ] = ( 1 ) n 1 ( n 1 ) ! F n 2 \begin{aligned} \alpha_n & = \; \frac{1}{\sqrt{5}(n-1)!}\sum_{u=1}^n (-1)^{n-u}\binom{n-1}{u-1} \big[\phi^u - \psi^u\big] \; = \; \frac{1}{\sqrt{5}(n-1)!}\sum_{u=0}^{n-1} (-1)^{n-1-u}\binom{n-1}{u} \big[\phi^{u+1} - \psi^{u+1}\big] \\ &= \; \frac{1}{\sqrt{5}(n-1)!}\big[ \phi(\phi-1)^{n-1} - \psi(\psi-1)^{n-2}\big] \; = \; \frac{1}{\sqrt{5}(n-1)!}\big[\phi(-\psi)^{n-1} - \psi(-\phi)^{n-1}\big] \\ & = \; \frac{1}{\sqrt{5}(n-1)!}\big[(-\psi)^{n-2} - (-\phi)^{n-2}\big] \; = \; \frac{(-1)^{n-1}}{\sqrt{5}(n-1)!}\big[\phi^{n-2} - \psi^{n-2}\big] \; = \; \frac{(-1)^{n-1}}{(n-1)!}F_{n-2} \end{aligned} On the other hand we know that G n + 1 ( X ) G n ( X ) G_{n+1}(X) - G_n(X) is a degree n n polynomial that vanishes at 1 , 2 , . . . , n 1,2,...,n , and so there is a constant β \beta such that G n + 1 ( X ) G n ( X ) = β ( X 1 ) ( X 2 ) ( X n ) G_{n+1}(X) - G_n(X) \; = \; \beta(X-1)(X-2)\cdots (X-n) From this it is clear that β = α n + 1 \beta = \alpha_{n+1} is the leading coefficient of G n + 1 ( X ) G_{n+1}(X) . Putting X = n + 1 X = n+1 we see that G n + 1 ( n + 1 ) G n ( n + 1 ) = α n + 1 n ! F n + 1 e F n + 1 = ( 1 ) n F n 1 \begin{aligned} G_{n+1}(n+1) - G_n(n+1) & = \; \alpha_{n+1} n! \\ F_{n+1} - {}^eF_{n+1} & = \; (-1)^n F_{n-1} \end{aligned} so that lim n F n e F n F n = lim n F n 1 F n + 1 = ϕ 2 = 1 2 ( 3 5 ) \lim_{n \to \infty} \frac{|F_n - {}^eF_n|}{F_n} \; = \; \lim_{n \to \infty}\frac{F_{n-1}}{F_{n+1}} \; = \; \phi^{-2} \; = \; \boxed{\tfrac12(3 - \sqrt{5})} using Binet's Formula again to evaluate this limit.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...